LOGISTICS DISTRIBUTION PLANS DURING EMERGENCY RESPONSE IN INDONESIA WORLD FOOD PROGRAM - Hidayat, Raden Didiet Rachmat; Deswari, Maya; Suhalis, Adenan (Jurnal Manajemen Bisnis Transportasi dan Logistik, 2017)
Taking into consideration the geographical location of West Sumatra is prone to natural disasters, the Indonesian government and communities should prepare well for dealing with natural disasters that may be happen anytime. One of preparedness needs to be done is to determine the entry point of logistical assistance as well as delivery route during the emergency response phase. Therefore, this research was conducted to plan for the logistics distribution during emergency response, designed by the World Food Program (WFP) as NGOs and leader of the international humanitarian community’s logistics coordination and response. This research used a qualitative descriptive analysis technique to describe the airports and ports to be used, as well as the transportation. As the result, Medan nominated as the main entry point for international actors while Jakarta as the main entry point of national actors. Furthermore, routes and modes of transportation that will be used for the delivery of relief items divided into three phases.